The Challenge of implementing universal primary education(UPE) in Uganda - Richard, Bukone Sajjabi (KDI School, 2011)
Universal Primary Education (UPE) was introduced in Uganda by the current political reign (the National Resistance Movement ? NRM) under the leadership of H.E General Yoweri Kaguta Museveni ? the President of the Republic of Uganda in 1997. Whereas the program was initially intended to provide free education for four primary school going age children from each family throughout the country, two years later (1999), the president announced what he called “Free Education for All” covering all the primary school going age children in the country. While the programme has registered a wide range of success since its inception, a number of challenges have equally affected its smooth progress and successful implementation up to today. This paper therefore sought to investigate the role and success of UPE and examine the challenges facing the implementation of the programme in Uganda. This study examined the challenges of implementing UPE in Uganda. It specifically examined the role and achievements so far registered by government in implementing the program and established the major challenges of its successful implementation. The study also examined the effect of large classes on UPE outcomes in Uganda and established possible measures for the success and effective implementation of UPE in Uganda. The study was qualitative and quantitative in nature. It was carried out using a cross sectional survey design and the data was collected using a close-ended self-constructed structured questionnaire and interview guides. The findings of this study indicated that lack of enough infrastructure coupled with large classes, high teacher-pupils’ ratio, the poor policy design and implementation, poor teacher quality, which is a function of poor teacher education and the high school drop-outs are a challenge to the implementation of the UPE program in Uganda. However, despite all these, government has registered significant achievements, which among others include the increase in pupil enrolment in government schools and improved level of literacy. Therefore, whereas there are challenges, a number of achievements have since been registered.
Thesis(Master) --KDI School:Master of Public Policy,2011
Keywords: Uganda.